About problem of transformation degraded and few-productive lands in land management system - Rafalska, L.; Zayachkivska, B. (Land Management, Cadastre and Land Monitoring, 2017)
The total area of eroded  areas is 31% of Ukrainian territory and exceeds 45% in the Sothern part of the state where percentage of forest lands averages just 2-5%. On the one hand we have the problem of the growth areas of degraded and few-productive land whose use for other purposes is economically inefficient. On the other hand, indicators of forest radically different from optimal. The solution to both problems is possible through the use of land transformation method of afforestation. Pubescent oak is considered as one of indispensable wood specie for eroded lands forestation under extreme conditions of Ukrainian steppe. It is different of highly drought-stability, do not damageing by insects and diseases. Proved that Pubescent oak has advantages over other species, characterized biological stability and durability and multifunctional properties.Special attention is paid to the role of fallen leaves in saving the fertile top layer of soil. Pubescent  oak forms a large quantity of fallen leaves, which is able to retain water and skip its excess, warning washing out soil surface and vertical erosion, protects the soil from drying and more. Technology of planting stock cultivating, tillage, optimization of patterns of wood species compounding, seeded placement and culture schemes with participation of Pubescent oak arc described. Thus, depending on the steepness  slopes of soil preparation and afforestation have their own characteristics.Investigated the cultivation of planting material, defined the better depth of planting (autumn - 7 cm, spring - 5 cm) and the better seeding rate (75-100 pieces per meter). Also the best select breed for  Pubescent oak are maple Tatar, dogwood, hawthorn and svydyna .Proved that placing a culture of  seating places in  rows  has advantages over the planting area. Powered care of the soil between the rows appropriate conduct during the years of the scheme 5-4-3-2-1.Revealed that reforestation of degraded land unproductive and positive impact on the surrounding usable land.Keywords: Pubescent oak, cultivation technology of planting material, soil preparation, circuit mixing of species, placement of planting seats, the composition of crops.